2018
DOI: 10.1155/2018/5985131
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Pembrolizumab-Induced Reactivation of Hepatitis B

Abstract: Hepatitis B virus (HBV) infection is common across the world, especially in Asia, Africa, Southern Europe, and Latin America. The association of HBV infection in patients suffering from different oncological conditions is well established. Many cases of HBV reactivation have been reported in patients on immunosuppressive chemotherapy and in patients undergoing hematopoietic bone marrow transplantations. Only one case has been reported so far of HBV reactivation in a patient treated with programmed cell death r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 17 publications
(20 reference statements)
1
51
0
Order By: Relevance
“…61 Hepatitis related to exacerbation of HBV infection has also been reported in patients who were subsequently found to be HBsAg positive. 62,63 The risk of reactivation in those who are only anti-HBc positive is thought to be low. 9 Interestingly, checkpoint inhibitors are also being investigated in the treatment of chronic hepatitis B by potentially overcoming the T-cell exhaustion that is observed.…”
Section: Specific Immunosuppressive Treatmentsmentioning
confidence: 99%
“…61 Hepatitis related to exacerbation of HBV infection has also been reported in patients who were subsequently found to be HBsAg positive. 62,63 The risk of reactivation in those who are only anti-HBc positive is thought to be low. 9 Interestingly, checkpoint inhibitors are also being investigated in the treatment of chronic hepatitis B by potentially overcoming the T-cell exhaustion that is observed.…”
Section: Specific Immunosuppressive Treatmentsmentioning
confidence: 99%
“…Unfortunately, there are limited published data describing the safety of anti-PD-(L)1 antibody for patients with advanced cancers and HBV infection. Several case reports have demonstrated that HBV reactivation does occur in some patients with resolved HBV infection during anti-PD-1 therapy [7–9]. However, the rate of HBV reactivation and potential risk factors are not defined.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 However, most immune-mediated hepatitis B reactivation cases have been reported in patients with severe immunodeficiency (after immunosuppressive chemotherapy or bone marrow transplantation). 10,35,36 In addition, in the rare cases where immunemediated reactivation of hepatitis B was not associated with profound immunosuppression, the episode was easily resolved after HBV antiviral treatment. 36,37 Thus, while the possibility of HBV reactivation should be considered, the risk of fatal hepatitis in immune-competent chronic HBV infection is low according to current available data.…”
Section: Discussionmentioning
confidence: 99%